Optimization of Psychological Wellbeing in Coronary Heart Patients through Mindfulness Therapy - Milya Novera; Anggra Trisna Ajani; Ricvan Dana Nindrea; Lidia Rusdi (STAI Publisistik Thawalib Jakarta, 2026)
Coronary artery disease (CAD) is one of the leading causes of morbidity and mortality worldwide, including in Indonesia. Patients with CAD frequently experience psychological burdens such as stress, anxiety, and depression, which negatively affect their quality of life and disease prognosis. At the community level, particularly in Puskesmas Lubuk Buaya, cases of coronary heart disease remain significant, while psychological support services are still limited. This situation highlights the urgency of integrating psychological interventions into community health services. This community service program aimed to optimize the psychological wellbeing of patients with coronary artery disease by implementing mindfulness therapy at Puskesmas Lubuk Buaya, as well as to enhance healthcare workers' capacity in applying a mindfulness-based approach in routine practice. This community service program was conducted from July to September 2025 using a community-based participatory approach. Activities included participant screening, psychoeducation, guided mindfulness practice, and independent home exercises. Quantitative evaluation demonstrated an increase in mean psychological wellbeing scores from pre- to post-program, indicating improved emotional regulation and perceived wellbeing among participants. These findings suggest that mindfulness-based community service activities may support psychological wellbeing in CAD patients and can be integrated as a complementary approach within primary healthcare settings.